Inhibition modulated by self-efficacy: An event-related potential study - Shi, Hong (Frontiers in Psychology, 2022)
Inhibition, associated with self-efficacy, enables people to control thought and action and inhibit disturbing stimulus and impulsion and has certain evolutionary significance. This study analyzed the neural correlates of inhibition modulated by self-efficacy. Self-efficacy was assessed by using the survey adapted from the Motivated Strategies for Learning Questionnaire. Fifty college students divided into low and high self-efficacy groups participated in the experiments. Their ability to conduct inhibitory control was studied through Go/No-Go tasks. During the tasks, we recorded students’ brain activity, focusing on N2 and P3 components in the event-related potential (ERP). Larger No-Go N2 amplitudes for the high self-efficacy group were found compared with the low self-efficacy group. Conflict detection as represented by N2 was modulated by self-efficacy, whereas conflict inhibition as represented by P3 was not modulated by self-efficacy. The highly self-efficacious students were more capable of detecting conflicts but not necessarily more capable of inhibiting action given that conflict was detected. Taken together, these findings offer neurophysiological evidence of the important regulatory role of self-efficacy in inhibitory control ability development.